Canada : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2010)
Canada has experienced drastic changes in its economy during the global financial crisis. This Selected Issues paper discusses the evolution of equilibrium real home prices in key Canadian provinces in the post-crisis period, Canadian dollar movement during and after the global financial turmoil in line with other world currencies, assessment of impacts on Canada's potential growth, development of Canadian automotive sector-namely, NAFTA partners during the crisis, and the role of Canada Mortgage and Housing Corporation (CMHC) in Canada's housing market.